Factors Causing Rework at Building Construction in The Department of Highways and Settlements of Aceh Province - T. Budi Aulia; . Mubarak; Rahmatul Irfan (Syiah Kuala University, 2012)
The operation of a building construction project should be carried out through aspecific management system. Construction project must also have a definite schedule and implementation plan. The general impact that would occur if the construction is not accordance with the schedule and plan is that the delays in project realization which would increase the cost of implementation. One of the factors causing such delays is due to the reworking activities on one or more items of the construction process. The purpose of this study is to determine the factors that cause rework on the building construction projects in the Department of Highways and Settlements in Aceh Province. The research methodology is descriptive qualitative to descriptive quantitative that explains the processed data based on the calculation of numbers. The instrument of this research was a questionnaire that asked to 55 respondents, consisting of 16 project owners, 23 contractors and 16 supervising consultants. This study was conducted to see the main factors of the rework on building construction projects. The results showed that a major cause of the rework in termof design and documentation was the unclear detail and the changed design; in term of managerial factors is lack of control of the project owner; and materials arrived late and the lack of working experience were major causes of rework in term of resource factors. It is recommended to the Highways Agency and Human Settlements in Aceh Province to tighten control over the project consultants and contractors to pay attention to the managerial problems and procurement of materials in accordance with schedule and work volume